2013
DOI: 10.1016/j.joca.2013.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis pain mechanisms: basic studies in animal models

Abstract: Osteoarthritis (OA) is a complex and painful disease of the whole joint. At present there are no satisfying agents for treating OA. The current standard of care mainly involves managing and alleviating its symptoms. Mechanisms of OA pain have been studied in rodent knee OA models produced by intra-knee injection of the chondrocyte glycolytic inhibitor mono-iodoacetate, surgery, or spontaneous development in some species. These models are clinically relevant in terms of histological damage and functional change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
112
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(120 citation statements)
references
References 90 publications
(113 reference statements)
5
112
0
3
Order By: Relevance
“…Matthew et al [10] further demonstrated the coexistence of increased central sensitization and referred pain, and suggested the existence of a central change in OA similar to that observed with neuropathic pain. Zhang et al [17] reported that OA pain correlated with peripheral and central sensitization, involvement of inflammatory cytokines, neuropeptides, and variety of chemical mediators. Hypersensitivity in OA has therefore been attributed to inflammation and degenerative changes within the ankle joint, as well as the excitability of intra-articular pain related receptors involving joint afferents.…”
Section: Discussionmentioning
confidence: 99%
“…Matthew et al [10] further demonstrated the coexistence of increased central sensitization and referred pain, and suggested the existence of a central change in OA similar to that observed with neuropathic pain. Zhang et al [17] reported that OA pain correlated with peripheral and central sensitization, involvement of inflammatory cytokines, neuropeptides, and variety of chemical mediators. Hypersensitivity in OA has therefore been attributed to inflammation and degenerative changes within the ankle joint, as well as the excitability of intra-articular pain related receptors involving joint afferents.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the observations that capsaicin reduces hyperalgesia and bone damage when given prophylactically (i.e., before MIA injection) in the rat (Kalff et al, 2010); however, in multiple clinical trials it showed no proven clinical benefit in patients with OA (reviewed in Remadevi and Szallasi, 2008). Clearly, OA is a complex disease with redundancy in pain pathways, and TRPV1 is only one of many pain targets in patients with OA (Killock, 2013;Zhang et al, 2013c).…”
Section: Transient Receptor Potential Channels: Acquired Diseasesmentioning
confidence: 99%
“…This is explained by the fact that pain perception comprises a complex series of neurophysiologic events involving stimulation, tissue response, transmission of pain signal and subsequent modulation of these at both peripheral and central levels (Ito and Creemers, 2013;Schaible, 2012). Inflammatory cytokines are important regulators of these pain mechanisms and their presence is associated with inflammatory pain arising from articular joints and IVDs (Ito and Creemers, 2013;Wuertz et al, 2012;Zhang et al, 2013). Interleukin-1 beta (IL-1ÎČ) and tumour necrosis factor alpha (TNF-α) contribute to disease progression and pain, by acting directly not only as nociceptive triggers, but also by inducing generation of other potentially nociceptive molecules, including nitric oxide and prostaglandin E (Liu et al, 2016;.…”
Section: Trpml2 -/-mentioning
confidence: 99%